MOTIVATING STUDENTS’ SPEAKING SKILL THROUGH SIMULATION IN BUSINESS ENGLISH CLASSROOM - An Action Research - Wienny Ardriyati (Universitas Stikubank (UNISBANK) Semarang, 2009)
This research proposed one of the approaches in teaching English in Economic Faculty at University of Stikubank. It aimed at using simulation in motivating students’ speaking skill in Business English class. It is a qualitative research and employs five data collection methods, namely: class observation, teaching journal, document collection, questionnaire and interview. The results show that the students are highly motivated and they feel that they get enough practice as well as theory. Kinds of simulation that are effective in Business Class are building company (making business plan), conducting meeting, doing negotiation and presentation. In addition, it was suggested that that the lecturer should give feedback to the students, create materials in the form of hardcopy and slideshow and provide games and or other activities in the lessons. Keywords: motivation, simulation, action research, business English, teaching journal.